Mortality in women following hip fracture - Weiss, Noel S.; Liff, Jonathan M.; Ure, Carol L.; Ballard, Jude H.; Abbott, G.Helen; Daling, Janet R. (Journal of chronic diseases, 1983)
The mortality of white female residents of King County (WA) 50–74 yr of age who sustained an isolated fracture of the hip ( n = 168) or lower forearm ( n = 217) during 1976–1979 was monitored during the 2 yr following the fracture. Among the women with hip fracture the (age-adjusted) percentages who died by the end of the first and second year were 5.9 and 10.5%, respectively. Among women with forearm fractures, the corresponding 1- and 2-yr percentages were 1.9 and 2.7%, values similar to that of white women of comparable ages in the population as a whole. The fact that women who broke their hip experienced a higher mortality rate than those who broke their forearm, while women in both groups were similar in having experienced trauma that led to a fracture, argues that it is the hip fracture and its consequences that lead to an increased death rate, rather than the factors that predispose to a fracture.